A Qualitative Exploration of an Interactive Digital Educational Roadmap for Pregnancy Health Literacy - Asih, Fransisca Retno; Christiana, Indah; Winarna, Nuristy Brillian Ainindyahsari (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2026)
Background: Many pregnant women have low health literacy, negatively affecting maternal and child health. Digital innovations offer potential solutions for health education, but no interactive roadmap specifically addresses pregnancy-related health literacy. Objective: This study explores the experiences, needs, and preferences of pregnant women and stakeholders in developing an interactive digital education roadmap to improve pregnancy health literacy. Methods: Using a qualitative descriptive design, in-depth interviews were conducted with 26 participants: six pregnant women, six husbands, two public health cadres, six midwifery students, and six midwives. Data collection involved face-to-face and online interviews, which were transcribed verbatim. Data analysis employed conventional content analysis, identifying themes and subthemes through coding and consensus. Triangulation and quotations ensured validity. Results: Three main themes emerged: (1) the urgency of health literacy, highlighting its role in knowledge, decision-making, adaptation, and misinformation prevention; (2) the need for comprehensive information on maternal health, fetal development, psychological support, nutrition, danger signs, and the husband's role; and (3) a preference for interactive digital roadmaps featuring attractive visuals, diverse media (infographics, videos, animations), cultural integration, accessibility, and ease of use. Conclusion: Developing interactive digital roadmaps as structured, user-friendly educational tools can enhance pregnancy health literacy. These innovations empower women and support healthcare providers and families. Integrating such tools into maternal health programs and establishing supportive policies can strengthen antenatal education and promote informed decision-making.